Heparin: Past, Present, and Future - Eziafa I. Oduah; Robert J. Linhardt; Susan T. Sharfstein (MDPI AG, 2016)
Heparin, the most widely used anticoagulant drug in the world today, remains an animal-derived product with the attendant risks of adulteration and contamination. A contamination crisis in 2007-2008 increased the impetus to provide non-animal-derived sources of heparin, produced under cGMP conditions. In addition, recent studies suggest that heparin may have significant antineoplastic activity, separate and distinct from its anticoagulant activity, while other studies indicate a role for heparin in treating inflammation, infertility, and infectious disease. A variety of strategies have been proposed to produce a bioengineered heparin. In this review, we discuss several of these strategies including microbial production, mammalian cell production, and chemoenzymatic modification. We also propose strategies for creating "designer" heparins and heparan-sulfates with various biochemical and physiological properties.